2022
DOI: 10.5993/ajhb.46.6.22
|View full text |Cite
|
Sign up to set email alerts
|

Management of Persistent Coccygodynia and Health Behavior: A Survey Study on Patients with Coccygodynia of Age 41 to 69 years

Abstract: Objectives: Coccygodynia, with trauma as a common etiologic factor, is a clinical condition of pain around the coccygeal region. This research aimed at investigating the level of satisfaction in surgical and non- surgical treatment of coccygodynia among Turkish patients and their health behavior. Methods: There is no dearth of studies on coccygodynia; however, a clear gap in research exists of studying coccygodynia patient satisfaction of specific age groups. Turkish patients aged 41 to 69 years and sufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[48] However, when patients’ weight was taken into account, a study found that overweight individuals were less satisfied with the coccygectomy. [49–51]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] However, when patients’ weight was taken into account, a study found that overweight individuals were less satisfied with the coccygectomy. [49–51]…”
Section: Discussionmentioning
confidence: 99%
“…[48] However, when patients' weight was taken into account, a study found that overweight individuals were less satisfied with the coccygectomy. [49][50][51] Infection in the wound was found in 2 cases after the surgical procedure (14.2%). The low infection rate is associated with the adoption of appropriate pre-operative and post-operative measures.…”
Section: Discussionmentioning
confidence: 99%